Conceptual design of harvesting energy system for road application - Mihaj, Kamarul Faiz (2013)
Energy harvesting becomes more and more important in our life. It refers to the practice of acquiring energy from the environment which would be otherwise wasted and converting it into usable electric energy. For this, every kind of energy can be exploited such as solar, wind or strain and kinetic energy. The idea is to propose a conceptual design that will carry out a suitable energy harvesting conversion to be applied for road application. Harvesting energy using piezoelectric generators has been chosen for this project. The project conduct a simulation analysis using a piezoelectric generator based on a model by S Roundy and P K Wright. The data used from a 15 mm x 3.2 mm x 0.14 mm single layer piezoelectric bending element which produce 0.95mW with a 1.727e6 Nm of input stress. The simulation is done using MATLAB-Simulink-SimPowerSystems which also tested with others value by Luigi Pinna et al.. Piezoelectric generator can be one of the green solutions for sustainable development in energy generation.